2016
DOI: 10.1167/16.15.10
|View full text |Cite
|
Sign up to set email alerts
|

Can (should) theories of crowding be unified?

Abstract: Objects in clutter are difficult to recognize, a phenomenon known as crowding. There is little consensus on the underlying mechanisms of crowding, and a large number of models have been proposed. There have also been attempts at unifying the explanations of crowding under a single model, such as the weighted feature model of Harrison and Bex (2015) and the texture synthesis model of Rosenholtz and colleagues (Balas, Nakano, & Rosenholtz, 2009; Keshvari & Rosenholtz, 2016). The goal of this work was to test var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Such a process is distinct from any single phenomenon such as source confusion, averaging or substitution but instead results from the broad spatial bandwidth of early stage filters. It is important to note that this model does not predict instances in which the magnitude of crowding is greatly modulated by certain configurations of flankers3361. We are not convinced, however, that these limitations argue against a population code; they instead require reconsideration of the way in which the features are weighted within the population code.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Such a process is distinct from any single phenomenon such as source confusion, averaging or substitution but instead results from the broad spatial bandwidth of early stage filters. It is important to note that this model does not predict instances in which the magnitude of crowding is greatly modulated by certain configurations of flankers3361. We are not convinced, however, that these limitations argue against a population code; they instead require reconsideration of the way in which the features are weighted within the population code.…”
Section: Discussionmentioning
confidence: 89%
“…We previously asked participants to report both the target and flanker orientations in an experiment similar to the present report, and found that participants were generally capable of reporting both elements, though they often reversed feature positions41 (see also ref. 61). Taken together, these data reveal that perceptual reports in clutter are probabilistic, but relatively fine detail can be recovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parametric texture model of Portilla and Simoncelli (Portilla & Simoncelli, 2000;Simoncelli & Portilla, 1998) extended this approach by additionally matching the correlations between channels and other statistics, producing more realistic appearance matches to textures. This model has since had broad impact on the field of human perception and neuroscience: the texture statistic representation may provide a fruitful way to understand the processing in midventral visual areas (Freeman & Simoncelli, 2011;Freeman, Ziemba, Heeger, Simoncelli, & Movshon, 2013;Movshon & Simoncelli, 2014;Okazawa, Tajima, & Komatsu, 2015;Ziemba, Freeman, Movshon, & Simoncelli, 2016), and it has been argued to provide a good approximation of the type of information encoded in the periphery, and thus a model for tasks such as crowding and visual search (Balas, Nakano, & Rosenholtz, 2009;Freeman & Simoncelli, 2011;Keshvari & Rosenholtz, 2016;Rosenholtz, 2011;Rosenholtz, Huang, & Ehinger, 2012;Rosenholtz, Huang, Raj, Balas, & Ilie, 2012)-though other evidence questions the more general adequacy of this representation for explaining crowding and peripheral appearance (Agaoglu & Chung, 2016;Clarke, Herzog, & Francis, 2014;Herzog, Sayim, Chicherov, & Manassi, 2015;Wallis, Bethge, & Wichmann, 2016).…”
Section: Studying Texture Perception With Parametric Texture Modelsmentioning
confidence: 99%
“…The parametric texture model of Portilla and Simoncelli (Portilla & Simoncelli, 2000;Simoncelli & Portilla, 1998) extended this approach by additionally matching the correlations between channels and other statistics, producing more realistic appearance matches to textures. This model has since had broad impact on the field of human perception and neuroscience: the texture statistic representation may provide a fruitful way to understand the processing in mid-ventral visual areas (Freeman & Simoncelli, 2011;Freeman, Ziemba, Heeger, Simon-celli, & Movshon, 2013;Movshon & Simoncelli, 2014;Okazawa, Tajima, & Komatsu, 2015;Ziemba, Freeman, Movshon, & Simoncelli, 2016), and it has been argued to provide a good approximation of the type of information encoded in the periphery, and thus a model for tasks such as crowding and visual search (Balas, Nakano, & Rosenholtz, 2009;Freeman & Simoncelli, 2011;Keshvari & Rosenholtz, 2016;Rosenholtz, 2011;Rosenholtz, Huang, & Ehinger, 2012;Rosenholtz, Huang, Raj, Balas, & Ilie, 2012)-though other evidence questions the more general adequacy of this representation for explaining crowding and peripheral appearance (Agaoglu & Chung, 2016;Clarke, Herzog, & Francis, 2014;Herzog, Sayim, Chicherov, & Manassi, 2015;Wallis, Bethge, & Wichmann, 2016).…”
Section: Studying Texture Perception With Parametric Texture Modelsmentioning
confidence: 99%